Grazing, egg production and carbon budgets for Calanus finmarchicus across the Fram Strait - Jenkins, Holly E.; Atherden, Florence; Cook, Kathryn B.; Anderson, Thomas R.; Thornton, Barry; Mitchell, Elaine; Jacob, Elodie; Mayor, Daniel J. (Frontiers in Marine Science, 2022)
Calanoid copepods comprise around 90% of Arctic zooplankton biomass and are fundamental to the ecological and biogeochemical functioning of high-latitude pelagic ecosystems. They accumulate lipid reserves during the productive months and represent an energy-rich food source for higher trophic levels. Rapidly changing climate in the Arctic may alter the quantity and composition of the food environment for one of the key copepod species, Calanus finmarchicus, with as yet unquantified effects on its production. Here we present rates of feeding and egg production in female C. finmarchicus exposed to the range of feeding conditions encountered across the Fram Strait in May/June 2018. Carbon (C) budgets were constructed and used to examine the relationship between feeding and growth (= egg production) in these animals. C-specific ingestion rates (mean ± standard deviation) were highly variable, ranging from 0.015 ± 0.004 to 0.645 ± 0.017 day-1 (mean = 0.295 ± 0.223 day-1), and were positively correlated with food availability. C-specific egg production rates ranged from 0.00 to 0.049 day-1 (mean = 0.012 ± 0.011) and were not correlated with either food availability or ingestion rate. Calculated gross growth efficiencies (GGE: growth/ingestion) were low, 0.12 ± 0.13 (range = 0.01 to 0.39). The assembled C budgets indicate that the average fraction of ingested food that was surplus to the requirements for egg production, respiration and losses to faecal pellets was 0.17 ± 0.42. We suggest that this excess occurred, at least in part, because many of the incubated females were still undergoing the energetically (C-) expensive process of gonad maturation at the time of sampling, an assertion that is supported by the relatively high C:N (nitrogen) ratios of the incubated females, the typically low egg production rates, and gonad maturation status. Ontogenetic development may thus explain the large variability seen in the relationship between egg production and ingestion. The apparently excessive ingestion rates may additionally indicate that recently moulted females must acquire additional N via ingestion to complete the maturation process and begin spawning. Our results highlight the need for improved fundamental understanding of the physiology of high-latitude copepods and its response to environmental change.